2007
DOI: 10.1074/jbc.m703695200
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes Responsible for Synthesis of Corneal Keratan Sulfate Glycosaminoglycans

Abstract: Keratan sulfate glycosaminoglycans are among the most abundant carbohydrate components of the cornea and are suggested to play an important role in maintaining corneal extracellular matrix structure. Keratan sulfate carbohydrate chains consist of repeating N-acetyllactosamine disaccharides with sulfation on the 6-O positions of N-acetylglucosamine and galactose. Despite its importance for corneal function, the biosynthetic pathway of the carbohydrate chain and particularly the elongation steps are poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 29 publications
(26 reference statements)
1
41
0
Order By: Relevance
“…However, in contrast to CHO cells, which do not produce keratan sulfate, MDCK cells synthesize significant amounts of this glycosaminoglycan (16,18), which is mainly composed of repeating disaccharide units containing Gal and GlcNAc, sulfated to a various degree. Elongation of the keratan sulfate molecule is performed by the sequential action of ␤4GalT4 and ␤-1,3-N-acetylglucosaminyltransferase 7 (␤3GnT7) (38). We showed that NGTdeficient MDCK cells exhibit a dramatic decrease in keratan sulfate production when compared with the wild-type cells, suggesting high dependence of ␤3GnT7 activity on NGT function.…”
Section: Discussionmentioning
confidence: 91%
“…However, in contrast to CHO cells, which do not produce keratan sulfate, MDCK cells synthesize significant amounts of this glycosaminoglycan (16,18), which is mainly composed of repeating disaccharide units containing Gal and GlcNAc, sulfated to a various degree. Elongation of the keratan sulfate molecule is performed by the sequential action of ␤4GalT4 and ␤-1,3-N-acetylglucosaminyltransferase 7 (␤3GnT7) (38). We showed that NGTdeficient MDCK cells exhibit a dramatic decrease in keratan sulfate production when compared with the wild-type cells, suggesting high dependence of ␤3GnT7 activity on NGT function.…”
Section: Discussionmentioning
confidence: 91%
“…The reaction sequence for the biosynthesis of KS consists of N-acetylglucosaminylation, 6-sulfation of a GlcNAc residue exposed at the nonreducing end, and galactosylation (Habuchi et al, 2006;Kitayama et al, 2007). Because GlcNAc sulfation at the C6 position is necessary for KS chain elongation (Kitayama et al, 2007), failure of this sulfation leads to loss of KS synthesis. That is, deficiency of human N-acetylglucosamine 6-O-sulfotransferase-5 (GlcNAc6ST-5) leads to loss of corneal KS synthesis (Akama et al, 2000), and lack of mouse GlcNAc6ST-1 causes loss of 5D4-reactive KS expression in the CNS (Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The 5D4 antibody is commonly used for detection of KS, and it has been demonstrated that 5D4-reactive KS is induced in a rat model of spinal cord injury (Jones and Tuszynski, 2002). The reaction sequence for the biosynthesis of KS consists of N-acetylglucosaminylation, 6-sulfation of a GlcNAc residue exposed at the nonreducing end, and galactosylation (Habuchi et al, 2006;Kitayama et al, 2007). Because GlcNAc sulfation at the C6 position is necessary for KS chain elongation (Kitayama et al, 2007), failure of this sulfation leads to loss of KS synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…␤4GalT5 and ␤4GalT6 are involved in the synthesis of lactosylceramide, which plays a major role in the regulation of cell proliferation, adhesion, migration, and angiogenesis. Recently, the importance of ␤4GalT4 in the construction of keratan sulfate chains, essential in the maintenance of corneal matrix structure, has been discovered (20). Interestingly, the ␤4GalT genes show sequence homology with those coding for ␤1,4-N-acetylgalactosaminyltransferases (␤1,4GalNAcTs), among them several enzymes are involved in chondroitin sulfate GAG chains synthesis.…”
mentioning
confidence: 99%